Effect of maturation level on normative specific-agility performance metrics and their fitness predictors in soccer players aged 11-18 years - Mohamed Sellami; Emna Makni; Wassim Moalla; Raghad Tarwneh; Mohamed Elloumi (BMC, 2024)
Abstract Background In sports sciences, normative data serve as standards for specific physical performance attributes, enhancing talent identification within a specific population. The aim of this study was to provide standard data for Agility-15 m, Ball-15 m tests, and skill index, considering maturation level, specifically age at peak height velocity (PHV). The study also investigated the relationship between relative performances in these tests and anthropometrics, jumping (squat jump [SJ], countermovement jump [CMJ]), and sprinting abilities (S-5 m, S-10 m, S-20 m, S-30 m) in young soccer players. Methods The study involved 647 soccer players aged 11-18 years, categorized into three groups: pre-PHV, circum-PHV, and post-PHV. Statistical analysis was conducted using analysis of variance and Bonferroni post hoc testing to detect variations among maturation groups, and Pearson's correlation test to examine the relationship between factors. Results Agility-15 m and ball-15 m performances among maturity groups showed significant differences (p < 0.01). Significant correlations were identified in pre-PHV group, between lower limb length and Agility-15 m (r=-0.23, p < 0.05) and between height and Ball-15 m (r=-0.23, p < 0.05). In post-PHV group, there was a correlation between body fat percentage (BF %) and Agility-15 m (r = 0.17, p < 0.05) and Ball-15 m (r = 0.21, p < 0.05). In all maturity groups, there were significant correlations between agility and sprint tests (S-5 m, S-10 m, S-20 m, and S-30 m) and muscle power (SJ and CMJ). Conclusion The study revealed that both speed and lower limb power significantly influence agility in young soccer players, providing valuable insights for coaches and practitioners to create tailored training plans and interventions for different age groups and maturity levels.